Characterization and Fabrication of the CFM-JTE for 4H-SiC Power Device with High-Efficiency Protection and Increased JTE Dose Tolerance Window - Wen, Yi (Nanoscale Res Lett, 2020)
A 13.5 kV 4H-SiC PiN rectifier with a considerable active area of 0.1 cm(2) is fabricated in this paper. Charge-field-modulated junction termination extension (CFM-JTE) has been proposed for satisfying the requirement of ultra-high reverse voltage, which enlarges the JTE dose tolerance window, making it approximately 2.8 times that of the conventional two-zone JTE. Besides, the CFM-JTE can be implemented through the conventional two-zone JTE process. The measured forward current is up to 100 A @ V(F) = 5.2 V in the absence of carrier lifetime enhancement technology. The CFM-JTE structure accomplishes 96% of the theoretical breakdown voltage of the parallel plane junction with a relatively small terminal area of 400 μm, which contributes to achieving the Baliga’s figure of merit of 58.8 GW/cm(2).